Integrated Agriculture and Health Based Interventions: Case Study on Pathways to improved Nutrition. - Sharma, Indu. (Tufts University. Tisch Library., 2020)
This presentation is a case study on the Integrated Agriculture and Health Based Interventions (IAHBI) project.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy